Health Awareness and Consequences of Consanguineous Marriages - Nitin Joseph; K. Keshava Pavan; Keerthan Ganapathi; P. Apoorva; Parul Sharma; Jai Aditya Jhamb (SAGE Publishing, 2015)
Objectives: This community-based study was done to assess the awareness of people regarding the ill effects of consanguinity and to observe its association with various sociodemographic variables and complications among children. Methods: Houses were chosen by systematic random sampling method and any married person in each household was interviewed. Results: Only 35 (18.7%) out of 187 participants were aware of health hazards associated with consanguineous marriages. The prevalence of consanguineous marriages was found to be 23 (12.3%). History of consanguineous marriage was seen significantly more among illiterates ( P = .05) and respondents with parental history of consanguinity ( P < .001). The mean age at marriage was found to be significantly lower among women married consanguineously ( P = .05). Congenital anomalies ( P = .02) and low birth weight ( P = .05) was seen significantly more among children with parental history of consanguinity. Conclusion: Large-scale awareness campaigns are needed to address the ill effects of this seemingly innocuous cultural practice.